Burnout, self-rated general health and life satisfaction among teachers and other academic occupational groups - Till Beutel; Clemens Koestner; Philipp S. Wild; Philipp S. Wild; Philipp S. Wild; Philipp S. Wild; Thomas Münzel; Thomas Münzel; Manfred E. Beutel; Karl J. Lackner; Karl J. Lackner; Norbert Pfeiffer; et al. (Frontiers in Public Health, 2023)
IntroductionTeachers work in a job with specific demands that can strain individual coping capabilities and can pose a risk for the development of psychological problems. Prior studies showed that teachers – in comparison with other occupational groups – had high risks of job-related psychological exhaustion. In our study we compared teachers and other occupational groups on burnout, general life satisfaction and self-rated general health. In addition, we analyzed if sociodemographic and job-related factors were relevant predictors of these outcomes.MethodsWe analyzed data from a total of 1,500 subjects arising from the Gutenberg Health Study. Binary logistic regression models and descriptive statistics were calculated to determine potential differences between the occupational group membership and the predictive values of sociodemographic and job-related variables.ResultsThe occupational groups did not differ significantly in terms of burnout, self-rated general health and satisfaction with life. Logistic regression models showed which sociodemographic and job-related variables were associated with the outcomes. Female sex, part-time employment as well as work-privacy conflicts showed particular predictive relevance.DiscussionJob-related interventions for teachers should aim at specific strains, e.g., arising out of work-privacy conflicts where interventions should focus on support of female teachers.